Geo environmental analysis of the sanitary landfill site in the city of Samawah and the possibility of planning to choose the best site - Kafaa Eabdiallah Lifulawf Aljiashii , /Abbas Zaghir Muhaisi Al-M ariani ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2020)
A study of the sanitary landfill in the city of Samawah for the year 2018 was based on the geographical analysis in the shadow of the environmental and locational determinants and depending on the natural and human geographical data to arrive at planning for the selection of the alternative site corresponding to the environmental conditions as the research showed that the life span of the landfill site in the city of Samawah has ended, and is unfit as a site Sanitary landfill, and despite that it is still used to date, as it turned out that the current landfill site does not take into account the conditions followed in the process of selecting healthy landfill sites, and the research showed that a study was prepared on the criteria and conditions to be followed in the process of choosing healthy landfill sites, and it also emerged that it should be established Sanitary landfill sites in areas characterized by characteristics and standards that are unique to other areas, within the environmental determinants to reduce their harmful effects on the environment and people, and based on the foregoing, the best sanitary landfill site is the alternative site for a landfill in the city of Samawah, which is in conformity with the environmental health standards for establishing sites Landfill.